IPTEKS E-GOVERNMENT DALAM PELAYANAN PUBLIK PADA DINAS KOMUNIKASI DAN INFORMATIKA KOTA MANADO - Simbala, Angelica; Manengkey, Berkania; Pangerapan, Sonny (Universitas Sam Ratulangi, 2018)
Dinas Komunikasi dan Informatikaâ€ Kota Manado is a government institution engaged in communication and informatics, which in the government of Kota Manado, â€œDinas Komunikasi dan Informatikaâ€ is one of institution who operates E-Government system. E-Government itself is implementation of electronic-based system used to effective and efficiently enhance public service quality. The use of technology by E-Government enhance relationship between government and mutuals (people, enterpreneur, or other instances). The function of E-Government is to improve quality of public services, with the use of technology information. And can help process communication of the government to create a clean, transparent government, and to answer demands of change effectively. E-Government have 3 (three) types of relation, which is Government to Citizen, Government to Business, Government to Government. â€œDinas Komunikasi dan Informatika Kota Manadoâ€ have applied these 3 types of relation, where there are 13 applications developed to apply E-Government system in Kota Manado. This research is done with hope â€œDinas Komunikasi dan Informatika Kota Manadoâ€ can always continuously improve and inovate with the existing application, and have to do application upgrade from time to time. â€œDinas Komunikasi dan Informatika Kota Manadoâ€ have to do socialization regarding applications around people not just with social media, but directly go into every district in Kota Manado.Keywords : E-Government, Public service, Technology Information